2010
DOI: 10.1007/s10682-010-9367-4
|View full text |Cite
|
Sign up to set email alerts
|

Is there rapid evolutionary response in introduced populations of tansy ragwort, Jacobaea vulgaris, when exposed to biological control?

Abstract: Differences in the herbivore community between a plant's native (specialists and generalists) and introduced range (almost exclusively generalists) may lead to the evolution of reduced allocation to defences against specialist herbivores in the introduced range, allowing for increased allocation to competitive ability and to defences against generalist herbivores. Following this logic, the introduction of biological control agents should reverse this evolutionary shift and select for plants with life-history t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 70 publications
2
32
0
Order By: Relevance
“…The relationships between total PA concentration and feeding were positive for all four beetle species after phylogenetic correction (although these correlations were not significant), indicating that PAs are not deterrent. However, only adult feeding behaviour was measured in this study, and PAs may affect feeding efficiency, pupal weights, fitness, or development time of specialist herbivores, although another study showed that larval density of L. jacobaeae in the roots of J. vulgaris is significantly correlated with adult feeding (Rapo et al 2010). An absence of a strong effect of PA composition on host choice by Longitarsus spp.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The relationships between total PA concentration and feeding were positive for all four beetle species after phylogenetic correction (although these correlations were not significant), indicating that PAs are not deterrent. However, only adult feeding behaviour was measured in this study, and PAs may affect feeding efficiency, pupal weights, fitness, or development time of specialist herbivores, although another study showed that larval density of L. jacobaeae in the roots of J. vulgaris is significantly correlated with adult feeding (Rapo et al 2010). An absence of a strong effect of PA composition on host choice by Longitarsus spp.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, besides adult feeding, host use by herbivores is also affected by female oviposition and larval feeding behaviour. However, in the case of L. jacobaeae, the number of larvae tunnelling the roots of J. vulgaris in spring is significantly correlated with the number of shotholes recorded in the previous autumn on the same plants (Rapo et al 2010), indicating that adult feeding is a good indicator of host use by at least L. jacobaeae.…”
Section: Longitarsus Speciesmentioning
confidence: 92%
“…Recently, T. jacobaeae, L. jacobaeae and other specialist herbivores have been introduced into to the invasive areas as biological controls for combating the invasion of J. vulgaris for several years (McEvoy et al 1991;McEvoy and Coombs 1999). However, Rapo et al (2010) only found small differences between traits of invasive Jacobaea vulgaris populations (New Zealand and North America) with and without biological control history of L. jacobaeae but larger differences between native and invasive populations. It suggests that the recent introduction of the biological control agents did not yet cause a rapid evolutionary adaptation of J. vulgaris populations in the introduced range towards the native phenotype.…”
Section: Study Speciesmentioning
confidence: 99%
“…For instance, protection against generalist herbivores increased in invasive populations of S. jacobaea (Joshi & Vrieling, 2005), Jacobaea vulgaris (Rapo et al, 2010) and Brassica nigra (Oduor et al, 2011) compared to their native populations.…”
Section: Discussionmentioning
confidence: 99%